Authority of the Village Head in Efforts to Settle Land Disputes Based on Law Number 6 Year 2014 (International Journal of Scientific Research and Management (IJSRM), 2019)
The purpose of this study was to find out the procedure for land dispute resolution carried out by the Village Head, to find out the basis of authority of the Village Head in land dispute resolution efforts based on Law Number 6 of 2014 concerning Villages and to find out the legal strength of land dispute resolution. This type of research is normative legal research. The theory used in this study is the theory of dispute resolution, the theory of authority and the theory of legal certainty. The approach method used is the legislative approach, case approach, and conceptual approach. Based on the results of the study that the procedure for land dispute resolution carried out by the Village Head was carried out in several stages, namely: 1. complaints; 2. summons of disputing parties; 3. the process of deliberation; and 4. formulating the results of the agreement in the form of a Joint Peace Letter. The authority of the Village Head in an effort to resolve land disputes is Article 26 of Law Number 6 Year 2014 concerning Villages and Law Number 30 Year 2014 concerning Government Administration. The power of land dispute resolution law carried out by the village head in the form of a Peace Letter on land disputes made by the Village Head based on what has been agreed upon by the disputing parties, it can be said that what is stated in the Peace Letter is valid and applies as a Law for those who make it, in this case the parties to the dispute. The agreements are irrevocable for reasons which are sufficient by law.